Reliance on Pumped Mother's Milk Has an Environmental Impact - Genevieve Becker; Yvonne Ryan-Fogarty (MDPI AG, 2016)
Breastfeeding is an environmentally friendly process; however when feeding relies on pumped mother's milk, the environmental picture changes. Waste plastics and heavy metals raise concerns regarding resource efficiency, waste treatment, and detrimental effects on health. Reliance on pumped milk rather than breastfeeding may also effect obesity and family size, which in turn have further environmental impacts. Information on pump equipment rarely includes environmental information and may focus on marketing the product for maximum profit. In order for parents, health workers, and health policy makers to make informed decisions about the reliance on pumped mother's milk, they need information on the broad and far reaching environmental aspects. There was no published research found that examined the environmental impact of using pumped mother's milk. A project is ongoing to examine this issue.